Validation of endotoxin‐core antibodies in dried blood spots as a measure of environmental enteropathy and intestinal permeability. Issue 4 (13th March 2018) - Hoke, Morgan K.; McCabe, Kimberly A.; Miller, Aaron A.; McDade, Thomas W.
Abstract: Objective: To validate a method for measuring endotoxin‐core antibodies (EndoCAb) from dried blood spots (DBS)—drops of capillary whole blood collected and dried on filter paper—as an indicator of environmental enteropathy (EE) in infancy and early childhood. Methods: A commercially available enzyme immunoassay kit was adapted for use with DBS, with optimized steps for sample elution. Technical validation included analysis of linearity/recovery, precision and reliability, lower limit of detection, and correspondence between matched plasma and DBS samples. Validation in a field‐based setting was implemented with samples from Peruvian infants ( n  = 82; age = 2–33 months) collected at two time points six months apart. Results: A high correspondence between plasma and DBS levels of EndoCAb was observed ( R 2  = 0.93, P  < .001). The lower limit of detection was found to be 0.01 GMU/mL. Interassay coefficient of variation (CV) was 10.9% and 8.06% for low and high controls, respectively. Mean intra‐assay CVs were 3.22% and 1.83%, respectively. In a sample of Peruvian infants, EndoCAb levels increased with age as expected ( P  < .001). Age explained nearly 34.6% of the variance in EndoCAb across the sample. Conclusion: These findings demonstrate the validity and feasibility of measuring EndoCAb in remote field settings using minimally invasive DBS sampling.